Plant responses to high temperature and drought: A bibliometrics analysis - Cui, Yong; Ouyang, Shengnan; Zhao, Yongju; Tie, Liehua; Shao, Changchang; Duan, Honglang (Frontiers in Plant Science, 2022)
Global climate change is expected to further increase the frequency and severity of extreme events, such as high temperature/heat waves as well as drought in the future. Thus, how plant responds to high temperature and drought has become a key research topic. In this study, we extracted data from Web of Science Core Collections database, and synthesized plant responses to high temperature and drought based on bibliometric methods using software of R and VOSviewer. The results showed that a stabilized increasing trend of the publications (1199 papers) was found during the period of 2008 to 2014, and then showed a rapid increase (2583 papers) from year 2015 to 2021. Secondly, the top five dominant research fields of plant responses to high temperature and drought were Plant Science, Agroforestry Science, Environmental Science, Biochemistry, and Molecular Biology, respectively. The largest amount of published article has been found in the Frontiers in Plant Science journal, which has the highest global total citations and H-index. We also found that the journal of Plant Physiology has the highest local citations. From the most cited papers and references, the most important research focus was the improvement of crop yield and vegetation stress resistance. Furthermore, "drought" has been the most prominent keyword over the last 14 years, and more attention has been paid to "climate change" over the last 5 years. Under future climate change, how to regulate growth and development of food crops subjected to high temperature and drought stress may become a hotspot, and increasing research is critical to provide more insights into plant responses to high temperature and drought by linking plant above-below ground components. To summarize, this research will contribute to a comprehensive understanding of the past, present, and future research on plant responses to high temperature and drought.